2021
DOI: 10.1111/sdi.12966
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise achievement of high convection volume in post‐dilution hemodiafiltration: A prospective observational study

Abstract: High‐volume online hemodiafiltration (HDF) has been reported to reduce the patient's mortality. However, achieving a high convection volume is challenging. In this prospective study, we investigated the feasibility of achieving high‐volume HDF with ≥21 L substitution volume via modification of blood flow rate (BFR), needle size, and dialysis membrane. In 30 patients undergoing hemodialysis, we followed a stepwise protocol and gradually increased the BFR (280→300→330 ml/min; steps 1, 2, and 3) and needle size (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…After changing the dialyzer surface area, the blood flow rate and needle size were increased sequentially in the same manner (steps 5-8). In step 1, 13.3% of patients reached a substitution volume of ≥21 L, while 96.7% of patients achieved a high convection volume after step 8 [65]. In conclusion, it is not difficult to obtain an appropriate level of convection volume for high-volume HDF in the real world by increasing the treatment time, blood flow rate, needle size, dialyzer surface area, and filtration fraction using a stepwise protocol.…”
Section: Strategies To Obtain An Optimal Convection Volume For High-v...mentioning
confidence: 90%
See 1 more Smart Citation
“…After changing the dialyzer surface area, the blood flow rate and needle size were increased sequentially in the same manner (steps 5-8). In step 1, 13.3% of patients reached a substitution volume of ≥21 L, while 96.7% of patients achieved a high convection volume after step 8 [65]. In conclusion, it is not difficult to obtain an appropriate level of convection volume for high-volume HDF in the real world by increasing the treatment time, blood flow rate, needle size, dialyzer surface area, and filtration fraction using a stepwise protocol.…”
Section: Strategies To Obtain An Optimal Convection Volume For High-v...mentioning
confidence: 90%
“…1). Recently, Kim et al [65] reported in a prospective observational study that a sufficiently high convection volume could be obtained by appropriately adjusting the blood flow rate, needle size, and dialyzer surface area. In this prospective observational study, an 8-step stepwise protocol was applied to 30 patients receiving postdilution HDF.…”
Section: Strategies To Obtain An Optimal Convection Volume For High-v...mentioning
confidence: 99%
“…Several clinical factors are implicated in this endeavor. For practical reasons, these factors are described analytically and then implemented synthetically in a stepwise clinical approach 3,14,15 . Baseline patient's clinical condition represents the guiding factor of HDF prescription and initiation.…”
Section: Hdf Prescription: Factors To Be Consideredmentioning
confidence: 99%
“…A stepwise approach for implementing online HDF has been successfully achieved in several recent studies. 3,14,15 For practical reasons, prescription and clinical implementation of HDF is discussed according to three clinical conditions: first, in an incident dialysis patient; second, in a prevalent, stable, and regularly dialysis patient; third, in unstable patient or in case of unusual treatment schedule. This is presented in Figure 1.…”
Section: Clinical Implementation Of Hdf Therapy-stepwise Approach To ...mentioning
confidence: 99%
“…Hemoconcentration generally limits the filtration fraction to 20%–25% of the blood flow rate in postdilution HDF [ 3 ]. However, modern HDF machines have the option to run TMP-controlled mode during HDF by adapting the substitution flow according to the blood viscosity in the dialyzer [ 4 ]. Filtration fraction up to 30% can be achieved with TMP-controlled mode without excessive hemoconcentration.…”
mentioning
confidence: 99%